Pengaruh Pemodelan Elemen Tangga pada Gedung Beton Bertulang terhadap Beban Gempa: Studi Kasus Gedung Hotel Tajem Paradise City Yogyakarta 5 Lantai - Harsoyo, Yoga Aprianto (Universitas Muhammadiyah Yogyakarta, 2016)
Indonesia is a country that has a high seismic risk, so that the high-level buildings need to be designed to resist earthquake loads. Modeling of buildings generally use three-dimensional program. The designers usually model beams and columns as elements of the line and the rest, which were slab, shear wall and stairs modeled as two-dimensional elements or shell elements. Modelling stairs using shell elements can rigidify building. When structural elements in buildings are designed based on these conditions, it will be more vulnerable under seismic load. In this paper, it will be examined on effect of stair in buildings under earthquake load. The parameters that will be studied are building’s natural period, displacement between floors, and seismic forces that occur in the building. From this research, it is known that modeling without stairs will create a larger building’s natural period and displacement between floor so that modeling without stairs will make more conservative design structures against earthquake loads.